PENGARUH PENDEKATAN INTEGRATIF TERHADAP KETERAMPILAN MENYIMAK SISWA KELAS V SEKOLAH DASAR NEGERI GERENDENG 1 KOTA TANGERANG - Dede Fitriyani; Ina Magdalena; Asih Rosnaningsih; Sa’odah Sa’odah; Sumiyani Sumiyani (Jurnal Pendidikan Dasar, 2018)
Abstract : The first objective of this study was to find out whether there was an effect of listening skill on Indonesian language lessons by using the Integrative Approach for fifth grade students of SDN Gerendeng 1 Kota Tangerang. The method used in this study was quantitative experimental research (Quasi Experiment).The population is students in class V A and V B inGerendeng 1 Tangerang. The sampling technique used was purposive sampling technique. The data was obtained through pretest and posttest experiments. Trial the hypothesis using t-test obtained tcount = 1.42 and ftable = 2.00 at the signification level α = 0.05. So it can be concluded that there is no significant difference between the average pretest of the experimental class and the control class.As for the acquisition of the posttest hypothesis from the t-test results obtained tcount = 2,70 and ftable= 2.00 at the significance level α = 0.05, then concluded H0 is rejected and H1 is accepted that there are differences in listening skills between students who are given learning using the Approach Integrative with students who are not given learning using the Integrative Approach. From the data that has been obtained as stated, it can be concluded that there is an influence of the Integrative Approach to the listening skills of grade V students of SDN Gerendeng 1 Tangerang. Keywords: Integrative Approach, Listening skills